Perception Social of the Electromagnetic Technologies [Percepcion Social de Las Tecnologias Electromagneticas] - Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2016)
This article shows the results of the intervention in the communes of La Granja, Santiago and Ñuñoa belonging to the province of Santiago, in Chile. Such intervention reached the 1200 surveys to observe the perception of citizens regarding electromagnetic technologies and how are you impact their well-being. The operation was performed based on four dimensions: (i) Conscientious Use; (ii) Technology; (iii) Health; and (iv) Utility. The sample was characterized by age groups, educational level and working area. The results allows observing that there is a cognitive dissonance in different groups because they mention the importance of electromagnetic technology and at the same time recognize that they perceive the same technology as harmful to their health. This phenomenon is due to the High introduiction of the technologu in our daily life and the absence of education with respect to the usefulness of the technological device and with respect to the necessity of their use.